2020
DOI: 10.47104/ebnrojs3.v2i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stability of Nurses and its Relation to Their Job Crafting

Abstract: Context: Emotional stability is the process in which the personality is continuously striving for a greater sense of emotional health. Job crafting and can be seen as a specific form of proactive behavior in which the nurse initiates changes (redesign) in the level of job demands and job resources to make their job more meaningful. Nurses with high emotional stability are more tending to adapt to changes in their job and enhance their job crafting. Aim: This study aimed to assess the emotional stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…The positive value of the differences in the BAI scores between the pre-and postpracticum periods revealed that the post-practicum BAI scores decreased. This finding agreed with the point of view from Wang [4] and Saad et al [18], who mentioned that nursing students' anxiety level is higher in the initial period than in the follow-up period. If the practicum program lasted more than 3 weeks, the nursing students would adapt and their pre-practicum anxiety score might decrease to normal within 2-3 weeks after enrolling in the clinical setting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive value of the differences in the BAI scores between the pre-and postpracticum periods revealed that the post-practicum BAI scores decreased. This finding agreed with the point of view from Wang [4] and Saad et al [18], who mentioned that nursing students' anxiety level is higher in the initial period than in the follow-up period. If the practicum program lasted more than 3 weeks, the nursing students would adapt and their pre-practicum anxiety score might decrease to normal within 2-3 weeks after enrolling in the clinical setting.…”
Section: Discussionsupporting
confidence: 92%
“…Saad et al [ 18 ] concluded in their study that emotional stability was positively, highly significantly related to the job crafting of nurses. İspir et al [ 19 ] in their study showed that there was a correlation between personality traits and career adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced interpersonal relationship and positive work environment are crucial personal and job resources that predict job crafting. This cognitive mechanism acts as a collective process of intrinsic motivation that is expedited through cognitive flexibility and subjective cost-benefits analysis in the Indian context (Saad and Ahmed, 2020). Conclusively, the present study addresses the knowledge gap in the existing body of literature on the association of psychological detachment with job crafting along with intrinsic motivation, wherein emotional stability plays the role of mediator, especially in the Indian organization setting.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced interpersonal relationship and positive work environment are crucial personal and job resources that predict job crafting and employee engagement. This cognitive mechanism acts as a collective process of intrinsic motivation that is expedited through cognitive flexibility and subjective cost–benefits analysis in the Indian context (Saad and Ahmed, 2020). Therefore, this study adds to the previous literature by considering intrinsic motivation to be an integral part of individual personality domain (i.e.…”
Section: Discussionmentioning
confidence: 99%